EFFECT OF YOGA ON THYROID FUNCTION TESTS AND BIOCHEMICAL PARAMETERS IN PATIENTS SUFFERING FROM HYPOTHYROIDISM - Chawla Ranjna; Nair Rukamani; Mukherjee Somnath; Meitei Yendrenbam Ibotombi; Sood V R (International Journal of Applied Ayurved Research, 2020)
Aim: The aim was to study the effect of yoga on thyroid function tests and routine biochemical parameters in hypothyroid patients. Materials and Methods: Out of 100 patients of hypothyroidism, 83 completed the trial (41 in control and 42 in yoga group). The yoga group received intervention along with Thyroxine replacement and control group was given only Thyroxine replacement therapy. 45 minutes yoga session was given thrice a week for first 2 months and twice in a week for next 4 months. Levels of Thyroid function test, Anti-thyroid peroxidase (Anti-TPO), routine biochemical parameters including blood glucose, HbA1c, Liver function tests, Muscle related enzymes, Kidney function tests and Lipid profile were estimated. Results: There was significant increase in fT4 levels (p=0.001 for control and p=0.004 for yoga group), significant decrease in TSH levels (p=0.000 for both the groups) and significant decrease in Anti-TPO antibody levels (p=0.002 and p=0.02 for control and Yoga group respectively). In Control group decreased TSH levels did not meet the clinical euthyroid range whereas in the Yoga group normal TSH range was achieved. In Yoga group a significant decrease in fasting blood sugar (p=0.04) and cholesterol level (p=0.000) was observed. The amount of Thyroxine medicine taken by Control group increased significantly(p=0.000). Conclusion: Yoga helps in the better management of Thyroid function tests, and some biochemical parameters without any increase of Thyroxine medication. Clinical Significance: : Yoga as an adjunct therapy can be effective in controlling hypothyroidism.